Decolonization of Islamic Studies from Fazlur Rahman's Perspective: Integrating Qur'anic Ethics and Artificial Intelligence in Liberating Islamic Reasoning - Syukron, Ahmad; Lubis, Muhamad Riyadi (Tribakti: Jurnal Pemikiran Keislaman, 2026)
This study aims to analyze Fazlur Rahman's ideas within the framework of decolonizing Islamic studies by highlighting the relevance of Qur'anic ethics to the development of Artificial Intelligence. Through a qualitative approach based on text analysis and literature study, this research explores how Fazlur Rahman's dual method, specifically the dual movement from text to context, can be utilized as an epistemological instrument in liberating Islamic studies from the hegemony of secular and fragmented Western rationality. Decolonization in this context does not only mean liberation from Western methodological influence, but also the reconstruction of the Islamic scientific paradigm rooted in revelation and universal ethical values summarized in the terms Iman, Islam, and Taqwa. The integration of Qur'anic ethics with Artificial Intelligence is interpreted as an effort to bring moral awareness, social responsibility, and prophetic spirituality into the development of modern technology. The results of the study show that the values of faith, justice, trustworthiness, and benefit, as formulated by Fazlur Rahman, can be an ethical framework in responding to the moral challenges of using Artificial Intelligence. This research contributes to strengthening an autonomous, contextual, and human-oriented Islamic scientific paradigm, while also emphasizing the importance of liberating Islamic reasoning from the dominance of colonial epistemology in facing the digital era and the Artificial Intelligence revolution.